Ophthalmological Findings in Paediatric Non-Traumatic Coma in Enugu State University Teaching Hospital, Parklane, Enugu, Nigeria - Ikenna Kingsley Ndu; Ifeoma N Asimadu; Benedict Onyeka Edelu; Obinna Chukwuebuka Nduagubam; Ogechukwu F Amadi; Isaac Nwabueze Asinobi; Uchenna Ekwochi (Tropical Health and Medical Research, 2020)
The ophthalmological examination is a vital aspect of the central nervous system examination in comatose children. Several authors have documented different findings with disparities in their recommendations about making ophthalmological examination a routine in the management of the unconscious child. This study sought to evaluate the relevance of routine ophthalmological examination in the management of unconscious children admitted into the paediatric emergency room of Enugu State University Teaching Hospital, Parklane, Enugu, Nigeria. This was a prospective longitudinal study conducted from April 2018 to March 2019. Unconscious patients whose caregivers gave consent were recruited into the study. Traumatic causes of coma were excluded. Demographic features of the patients were obtained. The ophthalmologic examination and diagnoses were made by an ophthalmologist, while the emergency room pediatrician made clinical assessment and diagnoses. Sixteen unconscious children had ophthalmologic examinations done. The Glasgow coma scale scores ranged from 3 to 11, with a mean of 6.6±2.2. Thirteen (81.3%) of the children were classified as severe unconsciousness while the rest were moderate. The degree of unconsciousness was significantly associated with the outcome (?2 =16.0, P = 0.03). A total of six (37.5%) ophthalmologic diagnoses were made, which included cerebral malaria, degenerative myopia, orbital cellulitis, and exposure keratopathy. The presence of an abnormal ophthalmologic finding was not significantly associated with outcome (?2 =0.36, P = 0.55). Routine ophthalmologic examination may not be justified as a management protocol in unconscious children but may be considered in selected cases.